Integrated coseismic displacement derived from high-rate GPS and strong-motion seismograph: Application to the 2017 Ms 7.0 Jiuzhaigou Earthquake. (September 2021) - Guo, Bofeng; Di, Mingwei; Song, Fucheng; Li, Jingwei; Shi, Shuangshuang; Limsupavanich, Nutpapon
Highlights: Integration of GPS and strong-motion data for more accurate coseismic displacement. Novel model of fusing GPS and strong-motion data with baseline shift correction. Better performance of the integrated model shown in 2017 Jiuzhaigou earthquake. Abstract: Near-field coseismic displacement information is very important for seismological research. High-rate GPS and seismic sensors are mutually advantageous for capturing earthquake-induced coseismic displacements. The combination of them can help to improve the near-field observation results. In this paper, we propose a combined model of fusing GPS and strong-motion records by taking into consideration the corrections of baseline shift, and then apply a multi-rate Kalman filter to analyze the collocated GPS and strong-motion data. The performance of the proposed approach is validated using 1 Hz GPS data and 200 Hz strong-motion data collected within 150 km from the epicenter during the Ms 7.0 Jiuzhaigou earthquake occurred on August 8, 2017 in Sichuan Province, China (33.20°N, 103.82°E). It shows that the GPS displacements based on the Epoch-relative Positioning Approach well reflect the instantaneous motion state of stations during the earthquake, indicating that the maximum instantaneous displacement of SCJZ station is 3.2 cm in north and −2.0 cm in east, and the permanent displacement of SCSP station is −0.6 cm in north. More accurate and reliable broadband displacements less than 1 cm are obtained by the combination model, which provide the full spectrum of the seismic motion. The integrated displacements have more characteristics of strong-motion results in the early stage of the earthquake with less noise, and in the strong shaking period, tightly bound by the GPS displacements, the integrated displacements will not diverge, and thus accurately record the long-period information of seismic waves.